ESTIMATION ALGORITHM OF WEAR RATE ON TOOTH SURFACE AT CIRCULAR HELICAL-GEAR BREAKING-IN - Artem Yuryevich Lukonin (Advanced Engineering Research)
In the process of gearing breaking-in, teeth are worn down. The estimation algorithm of such wear rate in the circular helical point gearing is described. The algorithm performance is illustrated by the example of calculating the circular helical gearing with the circular tooth profile in the frontal cross section. The problem is solved using ANSYS software system of the finite-element analysis. The application of the developed algorithm for a finite-element model of meshing a pair of gearing teeth is described. The variation of the contact pressure surface distribution is analyzed in relation to the wear rate under the teeth breaking-in. The following is established. The gear with a circular tooth contour in the front cross section shows new properties compared to the gears with a linear or point contact. Breaking-in of the teeth in the gearing with circular contours is considered. In this case, under increasing the wear rate, peak contact pressures decrease and move from the mean line of the tooth to the tooth bearing centre.